Effects of Internationalization Rhythm and Speed on E-Commerce Firms' Growth and the Role of Institutional Distances - Bernhard Swoboda; Carolina Sinning (Management International Review, 2022)
In an increasingly digitalizing economy, e-commerce firms are known to internationalize faster and more irregularly than offline firms. However, it is important to analyze how e-commerce firms benefit from time-based internationalization decisions and whether they are still limited by institutional distances that are said to lose relevance, which we do not believe. We propose a theory-based framework to analyze the effects of e-commerce firms' internationalization rhythm and speed on their sales growth. Importantly, we apply multilevel modeling with cross-level interactions to provide insights into the role of institutional moderators, i.e., regulative, normative, and cultural-cognitive distances. We use data from 228 e-commerce firms that are operating Europe's leading online shops and 1702 market entries over 21~years. The results show that e-commerce firms exhibit stronger growth due to their irregular and fast internationalization process. However, this relationship changes depending on certain institutional distances, and different explanations regarding country-specific variances are provided. The findings have direct implications for managers interested in how online internationalization processes affect firm growth in light of the differing degrees of cross-country contextual differences among common institutions.
Keywords: 330; E-commerce firms; Online internationalization; Internationalization rhythm; Internationalization speed; Institutional distances